Sound source localization using window function filtering and weighted cumulative histogram method - Kang, H.; Choi, J. (IFAC Proceedings Volumes (IFAC-PapersOnline), 2012)
The importance of security cameras has been emphasised because of the effect of reducing crime rate. This paper describes a new approach to a sound source localization system and a new method for security cameras with an array of microphones in the outdoor environments. This study details the robust method to reduce the influence of environmental noises in the sound source localization using an array of microphones, the new approaches to enhance the time delay of arrival by filtering the general cross correlation's coefficient with accuracy and to calculate cumulative angles weighted by a general window function. ？ 2012 IFAC.